The effect of voluntary disclosure and financial distress on audit delay - Nurmala, Putri; Rahayu, Trisnawati; Adiwibowo, Akhmad Sigit (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2023)
This study examines the effect of voluntary disclosure and financial distress on audit delays in energy sector companies of Indonesia. We measure voluntary disclosure using a ratio scale, which shows the total score of disclosures filled with items of voluntary disclosure determined by BAPEPAM. Financial Distress is measured using a ratio scale proxied using the debt-to-equity ratio. Meanwhile, audit delay is measured using a ratio scale by calculating the difference in the audit report date minus the financial report date. The data analysis technique uses panel data analysis. Based on the test results, it stated that voluntary disclosure and financial distress had a positive and significant effect on audit delay simultaneously. Voluntary disclosure does not affect audit delay, while financial distress affects it positivelyAbstrakPenelitian ini menguji pengaruh pengungkapan sukarela dan financial distress terhadap audit delay pada perusahaan-perusahaan sektor energi di Indonesia. Penelitian ini mengukur pengungkapan sukarela berdasarkan skala rasio yang menunjukan total skor pengungkapan sukarela sebagaimana yang ditentukan oleh BAPEPAM. Financial distress dalam penelitian ini diukur dengan menggunakan debt to equity ratio. Sementara itu, audit delay diukur dengan skala rasio yang dikalkulasi berdasarkan perbedaan hari audit dan pelaporan keuangan. Penelitian ini menemukan bahwa secara simultan, pengungkapan sukarela dan financial distres berpengaruh positif terhadap audit delay. Namun secara parsial, pengungkapan sukarela tidak mempengaruhi audit delay, sedangkan financial distress berpengaruh positif